Neuroprotective Properties of Berberine: Molecular Mechanisms and Clinical Implications - Erjie Tian; Gaurav Sharma; Chongshan Dai (MDPI AG, 2023)
Berberine (BBR), an isoquinoline alkaloid natural product, is isolated primarily from Coptis chinensis and other Berberis plants. BBR possesses various bioactivities, including antioxidant, anti-inflammation, anticancer, immune-regulation, and antimicrobial activities. Growing scientific evidence underscores BBR's substantial neuroprotective potential, prompting increased interest and scrutiny. In this comprehensive review, we elucidate the neuroprotective attributes of BBR, delineate the underlying molecular mechanisms, and assess its clinical safety and efficacy. The multifaceted molecular mechanisms responsible for BBR's neuroprotection encompass the attenuation of oxidative stress, mitigation of inflammatory responses, inhibition of apoptotic pathways, facilitation of autophagic processes, and modulation of CYP450 enzyme activities, neurotransmitter levels, and gut microbiota composition. Furthermore, BBR engages numerous signaling pathways, including the PI3K/Akt, NF-κB, AMPK, CREB, Nrf2, and MAPK pathways, to confer its neuroprotective effects. This comprehensive review aims to provide a substantial knowledge base, stimulate broader scientific discourse, and facilitate advancements in the application of BBR for neuroprotection.